Whistleblowing Intention and Good University Governance - Sukirman,; Suryandari, Dhini; Hidayah, Retnoningrum; Kayati, Ima Nur; Pujiyanti, Lutfi; Rahayu, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Good university governance becomes an important aspect in efforts to improve the quality of education. There are several aspects that affect good university governance. One of them is whistleblowing. Therefore, this study examines the influence of attitudes, subjective norms, perceived control, on whistleblowing intentions. Next, examine the effect of whistleblowing intentions on the implementation of good university governance. The population is Semarang State University employees by applying convenience sampling techniques. The method of data analysis uses IBM SPSS 22. The results of the study show that attitude influences on whistleblowing intentions. Subjective norms positively influence the intention to do whistleblowing. Whistleblowing intention has a significant positive effect on the implementation of good university governance. However, perceived control has no effect on whistleblowing intentions. Hence, it is necessary to provide incentives for reporters to increase whistleblowing intentions